ISSUES WITH ARTIFICIAL INTELLIGENCE TECHNOLOGY APPLICATION IN THE AGRICULTURAL-INDUSTRIAL COMPLEX - Muhamediyeva, D.T.; Raupova, M. (SCIENCE and SOCIETY, 2025)
The article discusses the creation of guidelines for the cultivation of high-yielding crop varieties, taking into account soil fertility, and the creation of a program for assessing crop and land productivity based on blockchain technology and artificial intelligence mechanisms, which are applied to global successes. In addition, issues of modern information technology are analyzed improvement of soil quality, raw material processing and optimal management of product production.